Military Spending and Differential Accumulation: A New Approach to the Political Economy of Armament – The Case of Israel - Shimshon Bichler; Jonathan Nitzan (Review of Radical Political Economics, 1996)
This paper offers a new approach to the political economy of armament, focusing on the relationship between military spending and differential accumulation in mature capitalist economies. Applied to the “model” case of Israel, our analysis suggests that the militarization of Israel's economy since the late 1960s occurred within a growing dichotomy between large and small firms. The econometric model shows that the “military-bias” of Israeli industry raised the profits of the large corporate conglomerates but constrained and even lowered those of smaller companies.
Keywords: 330; arms; accumulation; capital; capitalism; centralization; conflict; conglomeration; corporation; crisis; development; distribution; dual economy; elite; finance; growth; Israel; labour; methodology; Middle East; military; national interest; ownership; peac